Developing Creative Activities on Digital Platforms through the Integration of Art and Technology - Aslonova Navro‘za Hoshim qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: Integrating art and technology provides a powerful framework for fostering students’ creative activities on digital platforms. This article explores how digital tools and interactive platforms can enhance artistic learning, improve design skills, and stimulate innovative thinking. By combining traditional art principles with modern technological resources, students develop competencies in composition, color harmony, and visual problem-solving. The study emphasizes practical strategies for implementing digital platforms in art education to increase engagement, collaboration, and creative output. The findings suggest that the integration of art and technology can significantly enhance students’ aesthetic judgment, creative confidence, and ability to produce original digital artworks.